Lung Recurrence of Papillary Thyroid Cancer Diagnosed With Antithyroglobulin Antibodies After 10 Years From Initial Treatment - Viola, David; Agate, Laura; Molinaro, Eleonora; Bottici, Valeria; Lorusso, Loredana; Latrofa, Francesco; Torregrossa, Liborio; Boldrini, Laura; Ramone, Teresa; Vitti, Paolo; Elisei, Rossella (Frontiers in Endocrinology, 2018)
INTRODUCTION Papillary thyroid cancer (PTC) is the most common endocrine malignancy. More than 98% of patients achieve an excellent response with no evidence of clinical, biochemical or structural disease after initial treatment. In these patients structural recurrence is rare, more frequently diagnosed in the first 5 years from initial treatment and almost invariably localized in neck lymph nodes. PATIENT We report the case of a woman affected by PTC who presented with rapidly rising anti-thyroglobulin antibodies (TgAb) level after 10 years from clinical, morphological and biochemical remission. DIAGNOSIS AND TREATMENT In 2003 a 56 year old patient was treated with total thyroidectomy and radioiodine remnant ablation (RRA) for a PTC (2 cm) with minimal extrathyroidal extension (T3N1aM0 according to the 6th AJCC TNM staging system) associated with diffuse lymphocytic thyroiditis. In 2004 the patient was free of disease defined as undetectable Tg after recombinant human TSH administration in the absence of TgAb and structural disease. Since February 2012 the appearance and progressive increase of TgAb titer was observed and in 2014 a 18FDG-PET scan documented three hypermetabolic lesions suggestive of lung micrometastases. The lung lesions were cytologically confirmed as PTC metastases. Both the primary tissue and the lung metastasis were positive for BRAF V600E mutation. The patient was treated with 131-radioiodine that showed radioiodine avid lung lesions that lose the ability to take up iodine at the following treatment. The patient is still alive and the lung lesions are growing slowly. CONCLUSIONS Structural recurrence in patients that demonstrated an excellent response after initial treatment for PTC is extremely rare, and distant metastases exceptional but possible. This case is peculiar because recurrence was early identified after 10 years from initial treatment for the presence of detectable TgAb in a patient that had an histological diagnosis of lymphocytic thyroiditis but with an atypical clinical presentation (normal thyroid at neck ultrasound and undetectable TgAb and anti-thyroid peroxidase antibodies). For this reason TgAb should be tested with Tg in patients with a history of lymphocytic thyroiditis, either histological or humoral, also when TgAb is in the normal range and not suggestive of autoimmune thyroiditis.